Feasibility study on harnessing daylight for short distance curved transmissions for room light - Md Firdaus Omar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose and goal of this final year project is to study the design method of reflective device channel to transfer the daylight illumination into the room. The conventional method is uesd flat channel can glare the user eyes. Thus, the objective of the final year project is to design a method provide suffcient indoor illumination using daylight and to analyze illumination data in order to control the lighting room.